Blood pressure and mortality in a prospective cohort of HIV-infected adults in Port-au-Prince, Haiti. Issue 7 (July 2018) - Batavia, Ashita S.; Severe, Patrice; Lee, Myung Hee; Apollon, Alexandra; Zhu, Yuan Shan; Dupnik, Kathryn M.; McNairy, Margaret L.; Pape, Jean W.; Fitzgerald, Daniel W.; Peck, Robert N.
Abstract : Objective: The objective of this study was to determine how baseline blood pressure and incident hypertension related to antiretroviral therapy (ART) initiation, HIV-related inflammation and mortality in HIV-infected adults in a low-income country. Methods: We conducted long-term follow-up of HIV-infected adults who had participated in a trial of early vs. delayed initiation of ART in Port-au-Prince, Haiti. Between 2005 and 2008, 816 HIV-infected adults were randomized to early ( N  = 408) vs. delayed ART (when CD4 + cell count <200 cells/μl or AIDS-defining condition; N  = 408). Blood pressure was measured every 3 months. Hypertension was diagnosed according to the Joint National Committee (JNC-7) guidelines. Biomarkers of inflammation and coagulation were measured from banked enrolment plasma samples. Survival analyses were performed using Stata 14. Results: The median age at enrolment was 39 years. The median follow-up time was 7.3 years. The hypertension incidence rate was 3.41 per 100 person-years, and was similar in early and delayed ART groups. In multivariable models, independent predictors of incident hypertension were older age, higher BMI and plasma interleukin (IL)-6 levels (adjusted hazard ratio, aHR = 1.23, P  < 0.001). Systolic pressure more than 140 mmHg at enrolment was associated with increased mortality (aHR = 2.47, P  = 0.03) as was systolic pressure less than 90 mmHg (aHR = 2.25, P  = 0.04). Prevalent and incident hypertension were also significantly associated with mortality. Conclusion: In a large prospective study of HIV-infected adults, we found a high incidence of hypertension associated with HIV-related inflammation. Baseline hypertension conferred a more than two-fold increased risk of death. Among HIV-infected adults in low-income countries, hypertension should be considered a serious threat to long-term survival.